Digital-based Technology to Preserve Sundanese Culture - M D Aulia; F R Dhynar; R I Arofah; K A Duanaputri (Peneliti.net, 2021)
The purpose of this research is to observe and inform Generation Z about the importance of knowing the local culture. The method used in this research is a descriptive method with observation and interviews to obtain information related to our subjects, such as what are the traditions, regional songs, and traditional games of Sundanese culture. The results of this research were calculated from the results of interviews and questionnaires that were distributed using a Google Form. It shows that almost 80% of the Generation Z had begun to forget that there was no Sundanese culture itself. It is due to the effect of the rapid development of technology and the entry and exit exchanges of western cultures that affect our native culture. With the restoration of Sundanese culture through digital technology, especially social media, it is hoped that Generation Z can return to the Sundanese culture. It is also hoped that they can preserve the almost forgotten Sundanese culture in creative ways that can attract many people to re-learn Sundanese culture. If digital media is used positively and used for education in introducing Sundanese culture interestingly, it will have a very good impact on the preservation of this Sundanese culture. This research concludes that we want to make Generation Z more familiar with local culture than foreign or western culture.